Awareness of computer vision syndrome and related factors among information technology professionals - Jayakumar, Gayatri G.; Thampi, Bindu; Iyer, Mahadevan K.; Sasidharan, Rekha R. (International Journal of Research in Medical Sciences, 2020)
Background: Extensive use of computers for both professional and personal purpose has led to an increase in computer related health problems. Aim of this study was to evaluate the awareness regarding symptoms and the related factors in computer vision syndrome (CVS) among a group of information technology (IT) professionals. Methods: This study was conducted among 300 IT employees. After obtaining informed consent, structured questionnaire was given and data collected and analyzed. Results: Out of 300 respondents, 194 (64.7%) were males and 106 (35.3%) females. Mean age was 30.5 years.48.3% had more than eight years of computer usage and 77.3% used computers on an average of 8-12 hours per day. About 201 (67%) of the participants had at least one ocular symptom, most common was dryness (96%). 94.7% reported eyestrain and 86.3% reported redness and itching. Dryness and eyestrain were more in males (p<0.05). Dryness, eyestrain and redness were more in those who used computers for more than eight years duration and for 8-12 hours/day (p<0.05). 253 (84.3%) were aware about this syndrome, the main source being internet. The main relief measure adopted was to take a break in between the work hours. Only 51.3% consulted a doctor for their symptoms. Conclusions: In our study though 84.3% of IT professionals were aware of CVS and 67% had at least one ocular symptom, only 51.3% took professional advice for their problems. There is a definite need for awareness about corrective measures and treatment methods to be adopted for CVS among IT professionals.